Ali Mustafa Yaqub dan Kontribusinya terhadap Pengembangan Literatur serta Dinamika Hadis di Indonesia - Rafiq, Muhamad Chaedar; Sa’adah, Dadah (Darul Yasin Al Sys, 2025)
Ali Mustafa Yaqub is a pivotal figure in the development of literature and hadith dynamics in Indonesia. Through his works and ideas, he significantly contributed to hadith studies, both methodologically and substantively. This research aims to examine Ali Mustafa Yaqub's contributions to hadith literature development, discussing hadith dynamics widely accepted as authentic, yet revealed as inauthentic. Focusing on his research and dissemination approaches, this study analyzes the impact on society and academia. The findings indicate that Ali Mustafa Yaqub's contributions extend beyond writing, encompassing deeper hadith understanding education and dissemination among Indonesians.